Protection of Children's Rights in the Application for Marriage Dispensation at the Sharia Court in Langsa - Shafia, Aqila (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
In Indonesia, one of the main issues related to child protection is underage marriage, where there is a difference between Law Number 16 of 2019 concerning marriage and Law Number 23 of 2002 concerning Child Protection in determining the age limit of children. This study aims to determine the factors that lead to the approval of marriage dispensation requests in the Sharia Court of Langsa and how children's protection rights in marriage dispensation requests are regulated in Law Number 23 of 2002 concerning Child Protection at the Sharia Court of Langsa. This research uses field research with a normative juridical approach. The results of the discussion on marriage dispensation requests in the Sharia Court of Langsa are submitted for reasons such as economic, low education, and pregnancy out of wedlock. The judge's decision in the dispensation of marriage cases, when related to child protection, does not fully provide the rights of children who are getting married. As stipulated in Law Number 23 of 2002 concerning Child Protection. However, on the other hand, the judge's decision in marriage dispensation cases is considered appropriate because it prioritizes the interests of the community, especially in urgent situations such as pregnancy out of wedlock and children getting married under age, the judge must ensure that the rights of the child are still obtained. [Abstrak: Di Indonesia salah satu masalah utama terkait perlindungan anak adalah perkawinan di bawah umur, dimana terdapat perbedaan antara undang-undang Nomor 16 Tahun 2019 tentang perkawinan dan Undang-undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak dalam menetapkan batas usia anak. Penelitian ini bertujuan untuk mengetahui apa yang menjadi faktor dapat dikabulaknnya permohonan dispensasi nikah yang terjadi di Mahkamah Syar’iyah Langsa dan bagaimana hak-hak perlindungan terhadap anak dalam permohonan dispensasi nikah dalam Undang-undang Nomor 23 Tahun 2002 tentang Perlindungan Anak pada Mahkamah Syar’iyah Langsa. Jenis penelitian yang digunakan penelitian lapangan (field research) dengan pendekatan yuridis normatif. Hasil pembahasan permohonan dispensasi nikah di Mahkamah Syar’iyah Langsa diajukan karena alasan ekonomi, pendidikan rendah, dan kehamilan di luar nikah. Putusan hakim dalam perkara Dispensasi Nikah jika dihubungkan dengan perlindungan anak memang belum sepenuhnya memberikan hak-hak anak yang akan menikah. Sebagaimana yang terdapat didalam Undang-undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak. Tetapi disatu sisi, putusan hakim dalam perkara dispensasi nikah dinilai telah sesuai dikarenakan lebih mementingkan kepada maslahat yang terjadi didalam masyarakat karena sesuatu yang urgent misalnya hamil diluar nikah dan anak harus menikah dibawah umur, maka hakim harus memastikan agar hak-hak anak tetap didapatkannya.]